Characterization of the thermo-mechanical properties of p-type (MnSi1.77) and n-type (Mg2Si0.6Sn0.4) thermoelectric materials. (November 2019) - Mejri, M.; Thimont, Y.; Malard, B.; Estournès, C.
Abstract: The thermoelectric generators reliability is highly sensitive to the materials they are made off. This work aims to characterize the structure, microstructure, emissivity and thermo-mechanical properties of p-type (MnSi1.77 ) and n-type (Mg2 Si0.6 Sn0.4 ) highly promising thermoelectric materials. In particular, the temperature dependence of the Young's modulus, evaluated by impulse excitation technique, shows for both materials values higher than those reported in literature. Fracture toughness measured by both single edge notched beam and indentation methods exhibits similar values to those reported in the literature. Micro-indentation measurements reveal that the hardness values of the MnSi1.77 are significantly higher than the Mg2 Si0.6 Sn0.4 one. Graphical abstract: Unlabelled Image